Give Jesus a hand! charismatic Christians : populist religion and politics in the Philippines - Kessler, Christl 1967- (Theology and religious studies / Agnes M. Brazal, series editor, 2008)
"Evangelical and Pentecostal churches have grown worldwide in the last decades. In the Philippines, this growth has not resulted in a decrease of the Catholic faithful, but in a Pentecostalization of Philippine Protestant Churches and the Philippine Catholic Church as well. In terms of numbers, the Catholic Charismatic movement is by far outnumbering the adherents of Evangelical and Pentecostal churches. This book explores the surge of Charismatic and Pentecostal Christianity using data from a nationwide survey with interviews and observations among Pentecostal churches and Catholic Charismatic groups. The authors question common perceptions of Charismatic Christians as under-privileged masses and depict the Charismatic success as a genuinely religious phenomenon, which nevertheless might have political repercussions. They transfer the concept of political populism to the religious sphere and explain the attractiveness and the ambivalences of Charismatic religion with the properties of populism. The potential political ramifications of the Charismatic success are ambiguous; it has the potential to strengthen the legitimacy of democratic institutions in the Philippines as well as the potential to foster theocratic attitudes."--Back cover.